Design, Synthesis, and Biological Evaluation of Lysine Demethylase 5 C Degraders. (16th February 2021) - Iida, Tetsuya; Itoh, Yukihiro; Takahashi, Yukari; Yamashita, Yasunobu; Kurohara, Takashi; Miyake, Yuka; Oba, Makoto; Suzuki, Takayoshi
Abstract: Lysine demethylase 5 C (KDM5C) controls epigenetic gene expression and is attracting great interest in the field of chemical epigenetics. KDM5C has emerged as a therapeutic target for anti‐prostate cancer agents, and recently we identified triazole 1 as an inhibitor of KDM5C. Compound 1 exhibited highly potent KDM5C‐inhibitory activity in in vitro enzyme assays, but did not show strong anticancer effects. Therefore, a different approach is needed for the development of anticancer agents targeting KDM5C. Here, we attempted to identify KDM5C degraders by focusing on a protein‐knockdown strategy. Compound 3 b, which was designed based on compound 1, degraded KDM5C and inhibited the growth of prostate cancer PC‐3 cells more strongly than compound 1 . These findings suggest that KDM5C degraders are more effective as anticancer agents than compounds that only inhibit the catalytic activity of KDM5C. Abstract : Chimeric compound : Compound 3 is a KDM5C degrader based on a KDM5C inhibitor and a ubiquitin E3 ligase recruiter. The prodrug form induces proteasomal degradation of KDM5C in prostate cancer PC‐3 cells and inhibits cell growth. KDM5C degraders are expected to be small molecules that modulate the epigenetic mechanism via KDM5C and may be therapeutic candidates for prostate cancer.